Faktor Risiko Hipertensi Pada Pasien Poliklinik Puskesmas Pajang Surakarta Hypertension Risk Factors in Polyclinic Patients of Pajang Public Health Center Surakarta - Sumardiyono .; Yusiska Wahyu I - Universitas Sebelas Maret Surakarta (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2017)
Abstract: Hypertension is a chronic disease, when blood pressure rises above normal blood pressure, ie systolic blood pressure 140 mmHg or more and diastolic blood pressure 90 mmHg or more. Patients with hypertension often don’t show symptoms and only realized the condition if hypertension has caused complications in the heart, blockage of blood vessels, until the rupture of blood vessels in the brain resulting in death, so hypertension is often referred to as